Controlled potato breeding zoned for the conditions of the Central Caucasus - U. Yu. Jabiev; V. E. Temirov; Z. A. Tsarikaev; S. S. Basiev (Новые технологии, 2025)
Introduction. Potato is one of the crops most susceptible to diseases. In the Russian Federation, the annual potato yield loss due to disease is 20-25 %. Stems and tubers serve as a substrate for the development of microorganisms, fungi and pathogenic bacteria. The risk of potato disease is possible both during the growing period and during storage.   The goal of the research is to create competitive varieties with high economically valuable traits, zoned for the North Caucasus region.   The methods. All records and observations were carried out according to the methods of the selection process.   As a result of the research, more than 200 varieties of various originators were used in the collection nursery of the Gorsk State Agrarian University. The work has been carried out in various directions for 23 years, including resistance to diseases and pests. Five varieties with high economic and biological indicators and productivity have been bred. As a result of the research, it has been found that hybrid offsprings of the 35th, 26th and 30th combinations have demonstrated high resistance of tops and tubers to famine fungus. 84.7 % of hybrid populations have demonstrated resistance to viral diseases. At present, the following hybrids have provided a competitive yield: 11.35/12 - 45.2 t/ha, 11.26/816 - 44.3 t/ha, 11.26/33 - 48 t/ha, 11.26/35 - 40.0 t/ha. The following hybrids have shown the highest stable quality indicators for starch and dry matter content: 11.35/12, 11.26/816, 11.26/594 - 16.2-16.8%, 22.2-22.8%, and their maximum accumulation has been noted in the hybrids of the 7th combination - from 17.4 to 24.4 % and from 23.3 to 30.5 %, respectively.   Conclusions. Thus, much attention has been paid to breeding in the direction of resistance of various potato varieties to a number of diseases.